Cancer-Related Concerns Among Women With a New Diagnosis of Gynecological Cancer: An Exploration of Age Group Differences. Issue 1 (1st January 2014) - Myers Virtue, Shannon; Manne, Sharon L.; Ozga, Melissa; Kissane, David W.; Rubin, Stephen; Heckman, Carolyn; Rosenblum, Norm; Graff, John J.
Abstract : Objective: The study aimed to characterize cancer-related concerns among women with a new diagnosis of gynecological cancer from a developmental life stage perspective. The study compared the degree of cancer-related concern between young women (45 years or younger), middle age women (46–64 years), and older women (65 years or older). Materials/Methods: Data from women (N = 243) with a condition diagnosed as primary gynecological cancer who were participating in a randomized control trial were analyzed. Women completed a measure that assessed the degree of concern in 12 cancer-related domains (physical functioning, cancer treatment, emotional functioning, sexual functioning, disease progression/death, own well-being, partner well-being, relationship with spouse/partner, body image, relationship with others, employment, and finances). Multivariate comparisons were made between the 3 age groups on the cancer-related concerns. Results: There were age group differences in overall cancer-related concern and specific cancer-related domains. Young women reported the greatest cancer-related concern ( P < 0.001). They reported greater concern over emotional functioning ( P < 0.001) and sexual functioning ( P < 0.001) compared to the middle- and older-age groups. Older women reported less concern over the impact of cancer on finances ( P = 007). There were no differences between age groups in concern over physical impairment, cancer treatment, disease progression/death, own well-being, partner well-being, relationship with spouse/partner, body image, and relationship with others. Conclusions: Age may play an important role in the impact of a gynecological cancer diagnosis in domains of functioning, specifically emotional functioning, sexual functioning, and finances. Other cancer-related areas may represent more universal degree of impact. Professionals may benefit from considering the impact of cancer from a developmental life stage perspective.